2013
DOI: 10.4049/jimmunol.1203288
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Follicular Th Cell Responses Are Impaired and Modulated by IL-4

Abstract: Newborns are characterized by poor responses to vaccines. Defective B cell responses and a Th2-type polarization can account for this impaired protection in early life. We in this study investigated the generation of follicular Th (TFH) cells, involved in the development of Ab response and germinal center reaction, upon vaccination in neonates. We showed that, compared with adults, Ab production, affinity maturation, and germinal center formation were reduced in neonates immunized with OVA–aluminum hydroxide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 38 publications
(46 reference statements)
7
62
0
2
Order By: Relevance
“…ICOS binding is well established to promote differentiation of Tfh [31] and OX40 engagement has been reported to promote generation, proliferation and survival of Tfh [3336]. Given the impaired generation of Tfh cell responses reported in infants [3739], targeting these cells holds promise for the development of more potent vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…ICOS binding is well established to promote differentiation of Tfh [31] and OX40 engagement has been reported to promote generation, proliferation and survival of Tfh [3336]. Given the impaired generation of Tfh cell responses reported in infants [3739], targeting these cells holds promise for the development of more potent vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies in mice sought to determine if newborns can mount effective T FH cell responses (86, 87). Both works showed that CD4 + CXCR5 + PD-1 + T FH cells can be induced in mice neonates subjected to antigenic immunization, but that their full development is impaired.…”
Section: Neonatal Follicular T Helper Cellsmentioning
confidence: 99%
“…Both works showed that CD4 + CXCR5 + PD-1 + T FH cells can be induced in mice neonates subjected to antigenic immunization, but that their full development is impaired. Indeed, neonatal T FH cells expressed lower levels of Bcl6 and IL-21 and were poorly located in GCs, while they were highly present in interfollicular regions (86). This localization outside of GCs correlates with the limited expansion and differentiation in GC T FH cells of newborn T FH cells (87).…”
Section: Neonatal Follicular T Helper Cellsmentioning
confidence: 99%
“…Important contributors to the poor antibody response in infants are impaired accessory cells, i.e., follicular Th (T FH ) cells (23) and follicular DCs (24), as well as inherent defects in B cell survival and differentiation (25). A potential contributor to diminished survival and differentiation is the reduced expression of B cell maturation antigen (BCMA) and BAFF-R on neonate B cells (26).…”
mentioning
confidence: 99%